2021
DOI: 10.1016/j.omtn.2021.01.023
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1-induced deacetylation of Akt expedites platelet phagocytosis and delays HEMEC aging

Abstract: Maintaining the health of the endothelium is of critical importance to prevention against cell aging. The current study was performed to clarify the role of sirtuin1 (SIRT1) in platelet phagocytosis in cell aging and identified its downstream molecular mechanism. Platelet phagocytosis by human endometrial microvascular endothelial cells (HEMECs) was characterized by transmission electron and fluorescence microscopy. Functional experiments were conducted to examine platelet phagocytosis and cell aging using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The second-ranked gene, Coiled-Coil Domain Containing 88A (CCDC88A), has also been associated with cancer and aging [ 44 , 45 ] and is involved in various biological processes, including tumor angiogenesis, cancer migration and invasion, tumor metastasis, and epithelial wound healing [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second-ranked gene, Coiled-Coil Domain Containing 88A (CCDC88A), has also been associated with cancer and aging [ 44 , 45 ] and is involved in various biological processes, including tumor angiogenesis, cancer migration and invasion, tumor metastasis, and epithelial wound healing [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being of interest due to its involvement in cancer and epithelial regeneration/repair [46], the role of CCDC88A in cell aging has also garnered interest due to its function as a direct downstream mediator of Akt signaling [45]. Lan et al (2021) observed in human endometrial microvascular endothelial cells (HEMECs) that the activation of CCDC88A, which is mediated by Sirtuin 1 (SIRT1) and its deacetylation of Akt and PDK1, which subsequently activate CCDC88A, results in delayed aging [45]. Both SIRT1 and Akt are involved in aging and have already been shown to play essential roles in HEMEC aging [45].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, researchers have found that the level of yeast Sir2 (a homolog of Sirt1) decreases as the increasing number of replications, which is one of the causes of yeast aging (Dang et al, 2009 ). Until now, accumulating scientific evidence indicates that the expression and activity of SIRT1 in mammalian cells decreased progressively with aging (Lamichane et al, 2019 ; Lin et al, 2020 ; Lan et al, 2021 ). This may be due to NAD+, the major cofactor of SIRT1, also shows a progressive decline with aging (Covarrubias et al, 2021b ).…”
Section: Expression and Activity Of Sirt1 Decreased In Aging Neurodegenerative And Metabolic Diseasesmentioning
confidence: 99%
“…[14] SIRT1 directly deacetylates NF-šœ…B, Akt, FoxO3a, and PGC-1š›¼ to regulate their nuclear translocation and/or activities. [15][16][17][18] A growing body of evidence suggests that activation of SIRT1 could ameliorate several skeletal muscle diseases such as cancer, aging, glucocorticoids, and chronic kidney disease-induced muscle atrophy. [19][20][21][22] Thus, SIRT1 seems to be an attractive therapeutic target for preventing skeletal muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%